Gandhi and the Terrorists: Revolutionary Challenges from Bengal and Engagements with Non-Violent Political Protest. Issue 3 (2nd July 2016) - Ghosh, Durba
ABSTRACT: Known for his advocacy of non-violence as a political strategy, this essay examines Gandhi's prolonged debates with revolutionary terrorists about the efficacy of non-violence. Over the course of three decades, Gandhi attempted to bridge the divide between non-violence and violent resistance, and recognised those who espoused political violence as embodying a shared sense of sacrifice and suffering; those who were jailed or detained for their crimes actively debated these strategies with him, even if they did not wholly agree about the efficacy of non-violence. The first two sections focus on Gandhi's engagements with the lives of two revolutionary terrorists who died as a result of their actions, Madanlal Dhingra and Gopinath Saha. The final section examines how two women revolutionary terrorists, Bina Das and Kamala Dasgupta, engaged with Gandhi and eventually joined his non-violent movement.